ANALYSIS OF THE QUALITY OF LIFE OF PATIENTS WITH INOPERABLE LUNG CANCER DURING RADIOTHERAPY AND PHOTODYNAMIC THERAPY - Yu. A. Ragulin; G. V. Afonin; E. E. Beketov; V. S. Usachev; V. N. Kapinus; E. I. Smolenov; A. A. Prigorodov; M. A. Kaplan; I. A. Gulidov; S. V. Gamayunov; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал, 2020)
Aim: to analyze the quality of life of patients with locally advanced inoperable lung cancer during radiation and photodynamic therapy. material and methods. the study included 59 patients with stage II–III lung cancer. the first group (Rt) included 28 patients, who received radical radiation therapy. they completed questionnaires before starting radiotherapy and 2–3 days before the completion of radiotherapy. the second group (PDt + Rt) included 31 patients, who underwent endoscopic photodynamic therapy followed by radical radiation therapy. they were interviewed three times: before PDt, 10 days after PDt (before radiation therapy), and 2–3 days before the completion of radiation therapy. two types of questionnaires were used: patient lung cancer symptom scale (Lcss) and EuroQol questionnaire (EQ-5D-5L). Results. the student’s t test and Mann-Whitney u test showed no statistically significant differences in symptoms (except for the symptom «blood in the sputum») between two groups. Both treatment options demonstrated improvement in most items assessing symptoms. In the Rt group, no statistically significant improvements in the item assessing pain were found. In the PDt + Rt group, no significant improvements in the item assessing cough were observed. a comparison of the data of the intermediate (after PDt) and the final questionnaire allowed us to establish that the items «appetite», «fatigue», «pain» and «the impact of the disease on life» improved only after the completion of full-course therapy. the improvement in the item assessing cough was observed after PDt; however, the treatment outcomes showed a return (worsening) of the symptom to the level, which was before treatment. the comparison of the data of the intermediate (after PDt) and the final questionnaire showed the improvement of the items, such as «mobility», «self-care», «daily activities» and «anxiety/depression» after PDt; however, the treatment outcomes indicated a return (worsening) of the symptom to the level, which was observed before treatment. Conclusion. Both types of questionnaires provided important information about the patient’s condition. Lcss questionnaires seem to be preferable in terms of the possibility of using parametric criteria and, as a consequence, obtaining quantitative data on changes in the health of patients. the analysis did not allow us to make a conclusion about the difference in the final efficacy Rt and PDt + Rt in terms of subjective assessment of the health status by the patients themselves. the use of questionnaires in the PDt + Rt group showed that after PDt (before starting Rt) patients had positive changes in their health, which were observed in the Rt group after the completion of full-course therapy.